(untitled) (Revista Educação, Artes e Inclusão, 2022)
When discussing studies on inclusive practices, we can often form a narrative as to how the inclusion of disability has been understood at different times: through segregation, the insertion of disabled individuals in social spaces, and through inclusive strategies that actively recognize the needs of each individual. Lately, another perspective has increasingly been in evidence: that of coopting disability and treating it as a product. Work by Mitchell and Snyder (2015) and Pelbart (2013) are of fundamental importance to understand this trend. The present article centers on examples from contemporary dance by artists such as Jérôme Bel and Claire Cunningham, intending to reflect on how normalization has affected the universe of body arts. Many dance troupes still work through a lens which reaffirms overcoming one’s limitations and erasing the singularity of one’s condition – by copying unimpaired bodies. Thus, we seek to identify normalizing processes, which have been recurring tropes in dance, but also to showcase those pieces which have succeeded in retaining the diversity of the differently-abled on stage. One hopes that this can lend support to studies of inclusion and the arts, by highlighting the creative potential of disabled artists when they are left unrestricted by normalization.